Natalie Wood reflections on a legendary life - Bowman, Manoah; Gregson Wagner, Natasha; Wagner, Robert 1930-; Redford, Robert 1936- (Running Press, 2016)
"The first family-authorized photographic study of Natalie Wood, and the first book to examine her glamorous film career as well as her private, off-screen life as a wife and mother"...Front jacket flap
Includes bibliographical references (pages 318-319)
Keywords: Wood, Natalie; Wood, Natalie -- Portraits; Motion picture actors and actresses -- United States -- Biography; Motion picture actors and actresses -- United States -- Portraits; USA; Biografie